2013
DOI: 10.3126/ajms.v4i3.8165
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile of blood stream infections among febrile patients attending a tertiary care centre of Western Nepal

Abstract: BackgroundBlood stream infections (BSI) are significant cause of morbidity and mortality in the world. This study was conducted to determine the common bacterial agents associated with BSI with their antimicrobial susceptibility patterns in a tertiary care centre in the Western region of Nepal. Method This cross-sectional study was conducted for a period of two years from May 2010 to May 2012. All patients with fever (temperature ≥ 38°C) were included in the study. Results A total of 4,145 patients with febril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Bloodstream infections are the leading cause of morbidity and mortality throughout the world [ 1 ]. Globally, around 200,000 cases of BSIs with mortality of rates ranging from 20 to 50% were reported annually [ 2 ]. In low- and middle-income countries including Ethiopia, BSIs are a major public health concern and cause illnesses and deaths in all groups of population [ 3 ], especially in immunocompromised individuals such as patients in an intensive care unit (ICU), elders, children [ 4 ], cancer patients [ 5 , 6 ], neonates [ 7 ], and patients living with human immunodeficiency virus (HIV) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bloodstream infections are the leading cause of morbidity and mortality throughout the world [ 1 ]. Globally, around 200,000 cases of BSIs with mortality of rates ranging from 20 to 50% were reported annually [ 2 ]. In low- and middle-income countries including Ethiopia, BSIs are a major public health concern and cause illnesses and deaths in all groups of population [ 3 ], especially in immunocompromised individuals such as patients in an intensive care unit (ICU), elders, children [ 4 ], cancer patients [ 5 , 6 ], neonates [ 7 ], and patients living with human immunodeficiency virus (HIV) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ciprofl oxacin and Gentamicin can be used as empirical antibiotics for the treatment of BSIs. 15 But the present study showed increased resistivity of pathogens towards Ciprofl oxacin. Whereas, Gentamicin still remains highly effective towards the isolates.…”
Section: Discussionmentioning
confidence: 89%
“…5 Higher occurrence of typhoid in the present study might have also occurred be due to the fact that the study was carried out during monsoon season. During this season where heavy rainfall occurs, there is 15 Bacteremia caused by coagulase-negative staphylococci is life threatening if not treated promptly. It is commonly responsible for infection in the immuno-compromised and might cause neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations